Textbook Economics – Understanding the self-image of a powerful discipline - Bäuerle, Lukas (Momentum Quarterly, 2017)
The extensive impact of economic science on other disciplines, society and politics is widely recognized. In order to deepen an understanding of this impact, the following paper aims at contributing to a profound comprehension of the economic discipline’s character. In fostering a reflection of economic science in its current condition I also seek to strengthen the public debate around this discipline. Referring to Thomas S. Kuhn’s concept of textbook sciences, the importance of textbooks in modern economics (science and education) is portrayed. With recourse to the discipline’s most important textbooks, I then reflect some of the economics’ key positions concerning its history, methodology and didactics and how they become mediated in the context of academic economic education.